IDENTIFICATION OF AMYLUM CHARACTERISTICS USING MICROSCOPIC - Findriyani Paus; Hasrul Abdullah; Agusrianto Yusuf (Journal of Health, Technology and Science (JHTS), 2023)
Starch is stored in permanent food reserves for plants, in seeds, core fingers, bark, roots of perennials, and tubers. Starch is 50-65% dry weight of wheat seeds and 80% dry matter of potato tubers. Starch is a type of polysaccharide that is widely found in nature, namely most plants are found in tubers, leaves, stems, and seeds.The purpose of this study was to identify the different types of starch, especially in potato, cassava, and rice. The method used in this research is the experimental method. The experimental method is an experiment conducted to prove a hypothesis by using potatoes, sweet potatoes and rice as samples for starch observations. The results showed that the modified potato starch (Solanum tuberosum) was white in color, curd, in the form of fine grains, odorless and tasteless. Microscopic examination showed the hilus was a point at a narrow end with clearly visible lamellae, a single starch arrangement. The characteristics of modified starch manihot utilissima are white ivory, in the form of fine grains, odorless and tasteless. Microscopic examination showed that the hilus is located in the middle, the lamellae are not clear, the arrangement of starch is single. The characteristics of rice starch (Oryza sativa) are ivory white, in the form of fine grains, odorless and tasteless. In the microscopic test showedhilum in the middle not clearly visible, no lamellae, single starch arrangement.